Deciphering tourist's conundrum:: unveiling influence of privacy risk perception on travel intentions and decision dynamics - md abu barkat ali (Revista Rosa dos Ventos - Turismo e Hospitalidade, 2025)
Privacy, a fundamental human need, significantly shapes travel decisions. This study innovatively compares perceived risk factors, notably privacy, often overlooked in prior research. This departure enriches our understanding of risk perception in travel. Exploring tourists' privacy preferences and residential locations as novel determinants, it offers crucial insights into travel behavior. Through quantitative methods involving 236 respondents, the study highlights privacy's pronounced impact on travel intentions. Variances in privacy perception across geographic landscapes underscore the interplay between privacy concerns, geography, and individual preferences. Advocating for privacy prioritization alongside traditional factors, it suggests tailored approaches to enhance trust, visitor satisfaction, and sustainable industry growth within our evolving technological era.